2021
DOI: 10.2334/josnusd.19-0504
|View full text |Cite
|
Sign up to set email alerts
|

Variability of salivary metabolite levels in patients with Sjögren’s syndrome

Abstract: Purpose: To investigate inter-and intra-individual variation in the levels and outputs (concentration multiplied by salivary flow rate) of salivary metabolites in patients with primary Sjögren's syndrome (pSS). Methods: A total of 56 samples of stimulated saliva were collected from 14 female pSS patients during four laboratory visits within 20 weeks and analyzed using proton nuclear magnetic resonance spectroscopy. Single saliva samples from each of 15 controls were also analyzed. Results: Among 21 quantified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 31 publications
2
29
0
2
Order By: Relevance
“…Eating and drinking were not allowed a minimum of one hour before the saliva sample collection. After collection, the saliva samples were immediately centrifuged and the supernatants were stored and transported as described in [ 6 , 9 ]. We demonstrate this study design in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eating and drinking were not allowed a minimum of one hour before the saliva sample collection. After collection, the saliva samples were immediately centrifuged and the supernatants were stored and transported as described in [ 6 , 9 ]. We demonstrate this study design in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Because patients typically suffer from hyposalivation, some samples were not sufficient for analysis with LC-MS or were poor quality. Saliva flow rates (mL/min) were calculated immediately after collection, as described previously (Herrala et al, (2021)). The Wilcoxon signed ranks test was used to analyze the salivary flow rate between the pre-medication and one week medication samples.…”
Section: Collection Of Salivary Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Because aging is a complex process that is influenced by a combination of genetics, the environment, diet, and lifestyles, metabolomics are becoming powerful tools to analyze the myriad of interactions and generate profiles of aging-related alterations in the body, thus providing better information about novel pathways and biomarkers and improving clinical approaches [ 22 ]. In the narrow field of salivary gland-related metabolomics studies, the majority of these studies focused on the discovery of disease biomarkers, from salivary gland-related diseases such as Sjögren’s syndrome to oral and periodontal diseases and to neurodegenerative diseases such as dementia, Alzheimer’s disease, and even cancers [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In Sjögren’s syndrome, metabolomics research using nuclear magnetic resonance (NMR) revealed that the concentrations of choline, taurine, alanine, glycine, butyrate, phenylalanine, and proline increased significantly in the saliva samples of Sjögren’s syndrome patients compared with healthy candidates.…”
Section: Metabolic Changes In Salivary Glandmentioning
confidence: 99%